Priprava, izvedba in pomen perceptivnih testov za fonetično-fonološke raziskave - Tivadar, Hotimir (Jezik in slovstvo, 2004)
The perception tests illustrated in the article, designes accroding to the Prague School of Phonetics, are an attmept to make the research and appropriate evaluation of spoken language objective, which will undoubtely contribute to the research of the Slovene language as something that can be empirically tested. What is really important in listening comprehension is an adequate design and implementation of testing certain phonetic properties. The focus of research was the recognition of certain segments (phonemes /e/ and /e!/, and /o/ and /o!/ and supra-segmental features (the phonological lenght of phonemes /a/, /i/ ,/u/).
Keywords: Slovene; slovenščina; fonetika; phonetics; fonologija; testi